2023
DOI: 10.1002/fsn3.3296
|View full text |Cite
|
Sign up to set email alerts
|

Mulberry extract upregulates cholesterol efflux and inhibits p38 MAPK‐NLRP3‐mediated inflammation in foam cells

Abstract: The accumulation of foam cells in arterial intima and the accompanied chronic inflammation are considered major causes of neoatherosclerosis and restenosis. However, both the underlying mechanism and effective treatment for the disease are yet to be uncovered. In this study, we combined transcriptome profiling of restenosis artery tissue and bioinformatic analysis to reveal that NLRP3 inflammasome is markedly upregulated in restenosis and that several restenosis‐related DEGs are also targets of mulberry extrac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Previous studies revealed elevated expression of the nucleotide binding domain-like receptor protein-3 (NLRP3) inflammasome in human atherosclerotic arteries and restenosis artery wall ( 133 , 134 ). A study showed that NLRP3 binding to ligands promotes inflammasome formation, activates caspase-1, and eventually promotes the maturation and secretion of IL-1β, and IL-18 ( 135 ).…”
Section: Mechanism Of Action Of Sglt2 Inhibitor In Preventing Coronar...mentioning
confidence: 99%
“…Previous studies revealed elevated expression of the nucleotide binding domain-like receptor protein-3 (NLRP3) inflammasome in human atherosclerotic arteries and restenosis artery wall ( 133 , 134 ). A study showed that NLRP3 binding to ligands promotes inflammasome formation, activates caspase-1, and eventually promotes the maturation and secretion of IL-1β, and IL-18 ( 135 ).…”
Section: Mechanism Of Action Of Sglt2 Inhibitor In Preventing Coronar...mentioning
confidence: 99%
“…The findings indicated that the ethanol extract potentially mitigates reactive oxygen species (ROS), diminishes oxidative stress, and suppresses phosphorylation in the mitogen-activated protein kinase (MAPK) pathway by downregulating p38, c-Jun N-terminal kinase (JNK), and extracellular signal-regulated kinase (ERK) expression, while rutin may solely achieve this through p38 inhibition in the MAPK pathway. Moreover, the study indicated a significant reduction in Malondialdehyde (MDA), increased superoxide dismutase (SOD) enzyme levels, and Glutathione (GSH) levels, which is a potent cellular antioxidant [10,14]. Furthermore, treatment with the extract and its fractions restored elevated nitric oxide (NO) production induced by LPS stimulation, primarily by downregulating the expression of inducible NO synthase [13,15].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the solid beverage MHP, which mainly consists of mulberry leaf aqueous extract and Hippophae protein peptides, showed protective potential against obesity and hyperlipidemia induced by a high‐fat diet in cellular and animal models. Interestingly, mulberry leaf has been traditionally used as a herb for lowering blood glucose and lipids, consistent with its high content of flavonoids and alkaloids (Liu et al., 2023 ; Zhang et al., 2022 ). On the other hand, Hippophae protein peptides are functional ingredients from Hippophae rhamnoides L. seeds, which have been shown to enhance insulin sensitivity and reduce lipogenesis (Wang et al., 2022 ; Yuan et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%